PERANAN VITAMIN B12 DALAM PENGENCER SUSU SKIM KUNING TELUR TERHADAP MOTILITAS DAN VIABILITAS SPERMATOZOA DOMBA SAPUDIPOST THAWING - Arini, Mirza Asafaizh; Suprayogi, Tri Wahyu; Warsito, Sunaryo Hadi; Sardjito, Trilas; Susilowati, Suherni; Triana, Indah Norma (Universitas Airlangga, 2019)
The purpose of this study was to prove that the addition of Vitamin B12 in egg yolk skim milk extender can maintain the motility and viability of post thawing Sapudi sheep spermatozoa. This study used sample of Sapudi sheep fresh semen that was collected with artificial vagina, and divided into 3 different treatments. The control treatment or P0, Sapudi sheep semen was diluted in the egg yolk skim milk extender + vitamin C 0,02 mg / ml, treatment group (P1 and P2), Sapudi sheep semen was diluted in the egg yolk skim milk extender+ vitamin B12 5 Î¼g / ml and grouped in P1, Sapudi sheep semen was diluted in the egg yolk skim milk extender + Vitamin C 0.02 mg / ml + Vitamin B12 5Î¼g / ml and grouped in P2. The data analysis was use One Way Analysis of Variant (ANOVA), then to identify the real difference among the treatments continued with Duncan distance test. The result of data analysis showed that P2 treatment was significantly different (p <0.05) with P1 treatment and P0 treatment or control. While P1 treatment was not significantly different (p> 0,05) with P0 treatment or control. The result showed that the addition of vitamin C 0.02 mg / ml with vitamin B12 5 Î¼g / ml combination in egg yolk skim milk extender was the best addition to maintain the motility and viability of the post thawing Sapudi sheep spermatozoa.